Morphological Study Of species of The Genus Convolvulus L. (Convolvulaceae) From Lattakia - لايقة سرحان; قره علي أحمد; سلطان عبير; زحلوط مياده (Latakia University Journal -Biological Sciences Series, 2022)
This research included morphological characteristics study of three species in Lattakia of genus Convolvulus L. (C. arvensis, C.cantabrica, C.betonicifolius), The study focused on the living shape, stem, leaves, calyx, petal, stamen, pistil, fruits and seeds. the results indicated that stem direction,leaf shapes,and micromorphological characteristics of sepals, stamens (filment,anther ) ,carpels ( style,stigma ) , fruits and Seeds hairs are considered the most morphological characters which show important morphological differences among the studying species. These can be considered among classification standards to help distinguish the studying species of Convolvulus L. genus Based on studied morphological characters, an identification key for the studying species is provided.